2011
DOI: 10.1213/ane.0b013e3182354b7e
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Hemostatic System During Cardiopulmonary Bypass

Abstract: Cardiopulmonary bypass (CPB) is a unique clinical scenario that results in widespread activation of the hemostatic system. However, surgery also results in normal increases in coagulation activation, platelet activation, and fibrinolysis that are associated with normal wound hemostasis. Conventional CPB interferes with normal hemostasis by diluting hemostatic cells and proteins, through reinfusion of shed blood, and through activation on the bypass circuit surface of multiple systems including platelets, the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
161
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(169 citation statements)
references
References 190 publications
2
161
0
6
Order By: Relevance
“…[15] However, fibrinogen also binds to the circuit, forming a binding site for platelets, only to be activated by the leucocytes. [16,17] Recent studies have demonstrated an association between the level of fibrinogen and postoperative blood loss, [18,19] and even suggested prophylactic supplementation of fibrinogen. [20] Similarly, in our study, the patients had critical or low fibrinogen levels; however, this study was not adequately powered to detect a difference between such low percentage change.…”
Section: Discussionmentioning
confidence: 99%
“…[15] However, fibrinogen also binds to the circuit, forming a binding site for platelets, only to be activated by the leucocytes. [16,17] Recent studies have demonstrated an association between the level of fibrinogen and postoperative blood loss, [18,19] and even suggested prophylactic supplementation of fibrinogen. [20] Similarly, in our study, the patients had critical or low fibrinogen levels; however, this study was not adequately powered to detect a difference between such low percentage change.…”
Section: Discussionmentioning
confidence: 99%
“…кардиология и сердечно-сосудистая хирургия, 5,2016 Интраоперационная кровопотеря является серьез-ным осложнением в хирургии и сопровождается ростом числа осложнений и смертности, увеличением продолжи-тельности и стоимости операции, послеоперационного пребывания в стационаре [1][2][3]. Вопрос кровопотери яв-ляется особенно актуальным в практике сердечно-сосуди-стого хирурга, так как нарушения свертывающей системы крови, связанные с применением искусственного крово-обращения (ИК), полная гепаринизация являются пред-располагающими факторами для геморрагических ослож-нений, затрудняющих достижение адекватного гемостаза [4,5].…”
unclassified
“…Вопрос кровопотери яв-ляется особенно актуальным в практике сердечно-сосуди-стого хирурга, так как нарушения свертывающей системы крови, связанные с применением искусственного крово-обращения (ИК), полная гепаринизация являются пред-располагающими факторами для геморрагических ослож-нений, затрудняющих достижение адекватного гемостаза [4,5]. Частота повторных операций по поводу кровотече-ний составляет до 2-6% у кардиохирургических пациен-тов, и, как правило, подобные вмешательства ухудшают прогноз [6,7].…”
unclassified
See 2 more Smart Citations